From clinic to community: A randomized controlled trial of a peer support model for adults with type 2 diabetes from specialty care settings in British Columbia. Issue 11 (2nd September 2022) - Tang, Tricia S.; Afshar, Rowshanak; Elliott, Thomas; Kong, Jason; Gill, Sabrina
Abstract: Aims: To examine the impact of a 12‐month peer‐led diabetes self‐management support intervention delivered via telephone amongst adults with type 2 diabetes (T2D) from specialty care settings in British Columbia (BC). Methods: One‐hundred ninety‐six adults with T2D were randomly assigned to either a 12‐month Peer‐Led, Empowerment‐based, Approach, to Self‐management Efforts in Diabetes (PLEASED) intervention or a usual care condition. PLEASED involved weekly telephone contacts from a peer leader (PL) in the first 3 months followed by bi‐weekly telephone contacts in the last 9 months. Assessments were conducted at baseline, 3 and 12 months. The primary outcome was HbA1c ; secondary outcomes included diabetes distress (DD), ApoB, systolic and diastolic blood pressure (BP), body mass index, waist circumference and depressive symptoms. Results: No within or between group changes were observed for HbA1c at 3 or 12 months. However, amongst participants with HbA1c  ≥ 69 mmol/mol (8.5%), the PLEASED group significantly lowered their HbA1c at 12 months [−11.7 mmol/mol (−1.07%); 95% CI: −20.7, −2.5 (−1.89, −0.23); p  = 0.016] compared to usual care. Amongst secondary outcomes, within‐group improvements in overall DD were found at 3 months (−0.21; 95% CI: −0.35, −0.08; p  = 0.002) for the PLEASED group and at 12 months for both groups (PLEASED: −0.35; 95% CI: −0.49, −0.21; p  < 0.001 and control: −0.33; 95% CI: −0.47, −0.19; p  < 0.001), however, no between‐group differences were observed. The PLEASED group improved systolic BP at 12 months (−5.4 mm Hg; 95% CI: −10.0, −0.8; p  = 0.023) compared to usual care. Conclusions: Participation in a peer support intervention in diabetes delivered via telephone leads to long‐term improvements in HbA1c amongst high‐risk adults with T2D living in BC. Trial registration: The study was registered on clinicaltrials.gov (NT02804620).